The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12185-018-2563-7
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant histone modifications induced by mutant ASXL1 in myeloid neoplasms

Abstract: An epigenetic modulator Additional sex combs-like 1 (ASXL1) is recurrently mutated in myeloid neoplasms such as myelodysplastic syndromes (MDS), acute myeloid leukemia (AML) and myeloproliferative neoplasms (MPNs). ASXL1 mutations are also frequently detected in clonal hematopoiesis with indeterminate potential (CHIP), which is the clonal expansion of premalignant hematopoietic cells without any evidence of hematological malignancies. Thus, understanding the roles of ASXL1 in hematopoiesis and myeloid neoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 77 publications
0
11
0
1
Order By: Relevance
“…These findings indicate that wild-type ASXL1 is a major tumor suppressor in hematopoiesis and suggest loss-of-function features of ASXL1 mutations ( 132 ). ASXL1 wild-type protein can also support H3K4 methylation through O-linked N-acetylglucosamine transferase (OGT) ( 44 ), H2AK119 ubiquitination through PRC1, and H3K27 methylation in specific loci. Mutations in ASXL1 were originally identified in MDS with del20q11 ( 133 ).…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…These findings indicate that wild-type ASXL1 is a major tumor suppressor in hematopoiesis and suggest loss-of-function features of ASXL1 mutations ( 132 ). ASXL1 wild-type protein can also support H3K4 methylation through O-linked N-acetylglucosamine transferase (OGT) ( 44 ), H2AK119 ubiquitination through PRC1, and H3K27 methylation in specific loci. Mutations in ASXL1 were originally identified in MDS with del20q11 ( 133 ).…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…BAP1-ASXL2, but not ASXL1-BAP1 complexes, appears to mediate this tumor-suppressive function; overexpression of BAP1 or ASXL2, but not ASXL1, induces senescence, and deletion of the ASXM domain of ASXL2 impairs senescence (human fibroblasts IMR90 cell line) [ 99 ]. While hematopoietic-restricted BAP1 loss in mice has been reported to lead to myeloproliferative [ 103 ] or MDS-like disease [ 104 ], somatic BAP1 mutations, unlike in some solid tumors (e.g., malignant mesothelioma and melanoma), are rarely present in myeloid malignancies [ 105 ]. Indeed, Dey et al reported that out of 32 patients with de novo MDS, a somatic BAP1 mutation was detected in one case [ 104 ].…”
Section: The Molecular Mechanisms Underlying Asxl1/2-mediated Hsc/hpc...mentioning
confidence: 99%
“…Within the histone modifiers, two frequently mutated genes have been identified in PMF: ASXL1 and EZH2. ASXL1 or additional sex combs-like 1, interacts with Polycomb group complexes (PgC), which are involved in histone modifications to continue gene expression [46,133,134]. Many studies have shown the importance of ASXL1 in normal hematopoiesis, but along with TET2, this gene is the second most common to be implicated in MPNs [46].…”
Section: Detection Of Somatic/acquired Non-driver Mutations or "Cooperating Mutations"mentioning
confidence: 99%